Korelasi Faktor Penyebab Kematian Pasien COVID-19 dan Penegakan Regulasi Penanganan COVID-19 di Kota Bogor - Indrianingrum, Yulia; Wiranta, Alma (Jurnal Bina Praja, 2021)
The outbreak of the COVID-19 virus has attacked all countries in the world and become a serious concern, also in Indonesia. Indonesia is trying to fight the spread of the COVID-19 disease with various forms of regulations issued, including the Government, Central Government, and District/City Governments. This policy was carried out to anticipate and prevent the spread of the COVID-19 virus outbreak. The study aims to look at the policies that the Bogor City Government has implemented and empirically test the data on COVID-19 patients to determine the factors that can influence the death of COVID-19 patients. The results showed that almost all COVID-19 patients adhere to the health protocol set by the Bogor City Government, but COVID-19 patients who are elderly, male, and have comorbid disease have a high risk of dying.